Five-Part Invention : a History of Literary History in Canada. - Blodgett, E. D. (University of Toronto Press, 2014)
Blodgett suggests that each of the several 'national' groups that compose Canada develops unique narratives that demonstrate their different responses to the notion of nationhood and their sense of place within Canada's borders.